The military footprint and its Argentine society: the historical service of the army - Codesido, Lucas (Revista General de Información y Documentación, 2022)
In this article we propose to give an account of the importance of the archive collections stored in the Historical Service of the National Army in Argentina. For this reason, we make a brief description of the history of the institution, the available records are described and the process of opening the archives linked to state repression is considered along with their treatment within the framework of new memorial scenarios that produce them. Then we offer a list of the available collections and a review about the consultation possibilities that the institution allows.
Keywords: Historical Service; Archives; Argentine History; Military Policy; Armed Forces